Business Education in Times of Pandemic: Compulsive Ritualism or Transformative Change? (GESTIÓN Y TENDENCIAS, 2021)
In response to the invitation extended to me by Gesten to review, revisit, and challenge business education in Chile, problematized in the current context of the pandemic, I accept that invitation because I consider such a reflective exercise to be timely.My account draws on my experience in a Business School where, from my position as a professor, I have observed and interpreted the guidelines —both formal and substantive— that the institution has followed over the course of the pandemic (Acuña, 2020). In that experience I also assume that these guidelines are not entirely unlike what probably occurs in other Business Schools, given that this educational industry tends to follow standards of institutional isomorphism that convey great similarity in the type of activities they carry out and the manner in which they perform them, beyond distinctive aspects of their identities (Alvesson and Willmott, 2001).